Some aspects of radiation safety on the territory of the Tomsk region; IV International Symposium on Radiation Safety, Obninsk, Sept. 25-27, 1996 - Rikhvanov L. P. Leonid Petrovich; Adam A. M.; Zubkov Yu. G.; Galtsova V. V. (1996, 1996)
В фонде НТБ ТПУ отсутствует